Drug Allergy in children: focus on beta-lactams and NSAIDs - Cravidi, Claudio; Caimmi, Silvia; De Filippo, Maria; Martelli, Alberto; Caffarelli, Carlo; Miraglia Del Giudice, Michele; Calvani, Mauro; Tosca, Maria Angela; Cardinale, Fabio; Marseglia, Gian Luigi; Manti, Sara; Chiappini, Elena; et al. (Acta Biomedica Atenei Parmensis, 2020)
Drug hypersensitivity reactions (DHRs) are adverse reactions to a drug. In children, most common drugs inducing such reactions include beta-lactams (BLs) and non-steroidal anti-inflammatory drugs (NSAIDs). The aim of the present work was to provide current knowledge on the management of DHRs in the pediatric population, focusing on BLs and NSAIDs hypersensitivity. The clinical feature of DHRs include immediate and non-immediate (delayed and accelerated) reactions, that may be severe or non-severe. A systematic approach to the patient based on the reported clinical history is essential to organize a safe and adapted allergy work-up. Skin tests are the first step to assess a possible DHRs, especially in immediate reactions to BLs. Drugs concentrations for these tests are standardized and validated. The drug provocation test remains the gold standard to reach a firm diagnosis. In selected cases, a therapeutic desensitization protocol may be proposed in children with a confirmed diagnosis of drug hypersensitivity. Clinicians should be aware of the diagnostic and therapeutic options, to provide the best management in children having experienced a history of DHR.